Interactive Online Karate Learning During the Covid-19 Pandemic - Sartono; Firman Adityatama; Nur Sulistyo Mutaqin; Kurnia Dyah Anggorowati Dyah Anggorowati (STKIP Muhammadiyah Kuningan, 2022)
The COVID-19 pandemic has affected the world in every aspect of our lives. This has had a huge impact on sport and learning. People have to adapt and change to maintain their normal activities. Learning and sports training are very important for young people. This study was conducted with the aim of knowing the training that can be carried out during the COVID-19 pandemic and local lockdowns. The research is focused on discussing changes in the way karate practices during the COVID-19 pandemic and what types of karate trainings are carried out during local lockdowns. The research method uses a survey. The research sample was 36 karate UKM students. The study was conducted using an online questionnaire. The results showed that 39% of students used online training through websites or applications, 25% of students used written training programs, 19% of students used video challenges, and 8% of students used video training and telephone conversations. The conclusion of the study shows that most students switch to online training using the Zoom application under social distancing rules and during local lockdowns